Developing Eight Dimensions of Graduate Profiles: A Case Study of Pre-service English Teachers in Indonesia - nor, hidayah (ELITE JOURNAL, 2025)
This study investigates the development of the eight dimensions of graduate profiles among pre-service teachers in Islamic university during their school-based teaching practice. Grounded in the framework of deep learning, the research employs a qualitative case study methodology. Data collection methods included classroom observations, analysis of reflective journals, and in-depth interviews with pre-service teachers who completed language curriculum development course. The results indicate that authentic classroom experiences facilitate comprehensive professional development. Pre-service teachers demonstrated critical thinking and problem-solving skills when adapting instructional strategies to diverse student needs. They exhibited creativity and innovation in designing effective learning activities. Collaboration and communication skills were enhanced through interactions with peers, mentors, and students. The responsibilities associated with serving as role models contributed to the cultivation of character and integrity. Engagement with contemporary issues promoted global citizenship awareness, while the integration of digital technologies improved digital literacy. Lesson planning and reflective practice supported self-directed learning, and classroom leadership responsibilities fostered leadership skills and a commitment to societal contribution. Despite challenges including inadequate facilities and inconsistent mentor support, the study highlights the significance of teaching practice as a deep learning experience. This process effectively integrates theoretical knowledge with practical application, preparing graduates who demonstrate academic competence, ethical conduct, adaptability, and social responsibility. The findings support Indonesia’s higher education objectives, which prioritize the development of holistic graduate profiles aligned with the requirements of the twenty-first century